A framework for establishing priorities in a country poverty reduction strategy - Duncan, Ron C., 1936-; Pollard, Steve; Asian Development Bank. Economics and Research Department (Manila : Asian Development Bank, 2002)
Reviews of history and progress of understanding of development theory for reducing poverty in developing countries.
' May 2002'
Includes bibliographical references (p. 16-17).
Keywords: Economic development; Poverty -- Developing countries